Drosophila melanogaster as an alternative animal model in fat metabolism studies - Dilan de Silva; Mangala Gunatilake (BLDE University Journal of Health Sciences)
Drosophila melanogaster is one of the most abundantly utilized model organisms today, in various contexts of biomedical research. It serves as one of the best alternative model organisms as it comprises most genes related to metabolism which are conserved in the human genome. The simplicity in genetics as well as their rapid life cycle makes it a righteous model organism that can be efficiently utilized in research. With the latest advances, numerous studies have disclosed the significance of using Drosophila as a model in studying fat metabolism and related diseases as well as potential therapeutic targets. It is discovered that Drosophila accommodates a range of cell types and organs which entail lipid metabolism and related energy homeostasis similar to those of mammals. Fat storage in Drosophila occurs in the form of lipid droplets carrying cholesterol and triacylglycerol which are accumulated primarily in the fat body – the analogous Drosophila organ to mammalian adipose tissue. Moreover, the Drosophila fat body has showcased its role in storage and metabolic regulation, akin to the function of the liver in mammals. Following a comprehensive overlook on Drosophila as a model organism in the study of fat metabolism, this narrative review covers lipid anabolic, enzymatic, and regulatory processes in Drosophila as well as the use of Drosophila in the study of fat metabolism associated diseases.